2018
DOI: 10.3390/buildings8080096
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Outdoor Views on Students’ Seat Preference in Learning Environments

Abstract: Abstract:A Good learning environment should support students' choices and attract them to stay. Focusing on outdoor views, this research explores two questions: How important outdoor views are in seat selection in learning environments? How do the view elements influence students' seating behaviors in learning environments? A seat preference survey and view elements and occupancy rate measurements were conducted in a university library building in Gold Coast, Australia. This study not only echoes the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Few studies investigated the influence of both daylight and outdoor view on visual performance [145,146]. For example, in a survey-based research [147] authors concluded that students prefer 'views' as the second priority before daylight availability in choosing seats. Other research conducted by [148,149] revealed people have a tendency to tolerate glare from windows if they have sufficient outdoor views especially when the source is a natural scene.…”
Section: Discussion On the Findingsmentioning
confidence: 99%
“…Few studies investigated the influence of both daylight and outdoor view on visual performance [145,146]. For example, in a survey-based research [147] authors concluded that students prefer 'views' as the second priority before daylight availability in choosing seats. Other research conducted by [148,149] revealed people have a tendency to tolerate glare from windows if they have sufficient outdoor views especially when the source is a natural scene.…”
Section: Discussion On the Findingsmentioning
confidence: 99%
“…Over recent decades, much consideration has been given to the effect of the physical environment of office buildings on the comfort, health and productivity of building users. In this regard, considerable effort has been expended to learn about the influence of the thermal, visual and acoustic aspects of buildings on occupant behaviours and expectations [1,2]. Building users and their productivity is influenced by various physical and behavioural components in an office environment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many of recent research papers are directed to university buildings in hot climates, where thermal comfort comes in first. Gou et al (2018Gou et al ( , 2020 collected energy use data from 80 university buildings in subtropical Australia in order to establish an energy benchmark system. They analysed energy consumption, energy use intensity and related space types and occupancy conditions.…”
Section: University Buildingsmentioning
confidence: 99%
“…This implied that optimizing space use and opening hours could reduce wasteful energy use for lighting and other building services. Gou et al (2018) studied impacts of outdoor views on students' seat selection and seating behaviours at workstations of a university library building in Australia. Workstations selected for the study are located in the periphery of the library space at level 3.…”
Section: Gou Et Al (mentioning
confidence: 99%